Pengaruh Ice Breaking Terhadap Minat Belajar Bahasa Indonesia Siswa Kelas IV Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis - Aisyah Nur Faidah; Alfi Satria; Anjar Sulistyani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
This study examines the effect of ice breaking on students' interest in learning Indonesian in class IV MI Muhammadiyah Sukajati Haurgeulis. The first main problem in this study is the lack of interest in learning Indonesian for fourth grade students. The second main problem is what types of ice breaking are suitable for Indonesian language lessons, and finally, I want to know whether there is an effect of ice breaking on the interest in learning Indonesian in the fourth grade students of MI Muhammadiyah Sukajati Haurgeulis. This study aims to determine the interest in learning Indonesian in fourth grade students, this study was also conducted to determine what types of ice breaking are suitable for Indonesian lessons, and to find out whether ice breaking has an effect on the interest in learning Indonesian in fourth grade students at MI Muhammadiyah Sukajati Haurgeulis. The research method in this study is using a quantitative approach, with observation, questionnaires, and documentation techniques. The population in this study were fourth grade students of MI Muhammadiyah, and the samples of this study were 15 students of class A as the experimental class and 15 students of class B as the control class. The results of this study indicate that there is a significant effect of ice breaking on the interest in learning Indonesian for fourth grade students, it can be seen that the results of a simple linear regression test show a significance value of Sig. 0.000 <0.05, it can be concluded that there is an influence between the independent variables on the control variable, the magnitude of the influence between the variables is 70%. The results of hypothesis testing the value of Asymp.Sig. (2-tailled) of 0.002 <0.05, it is said that H0 is rejected and H1 is accepted. Ice breaking that is relevant in learning Indonesian is ice breaking which is planned in advance and collaborated with the material to be taught.Keywords: Ice Breaking, Interest in Learning, Indonesian AbstrakPenelitian ini mengkaji tentang pengaruh ice breaking terhadap minat belajar Bahasa Indonesia siswa pada kelas IV Madrasah Ibtidaiyah (MI) Muhammadiyah Sukajati Haurgeulis. Pokok masalah utama pada penelitian ini yaitu rendahnya minat belajar Bahasa Indonesia pada siswa kelas IV. Permasalahan selanjutnya yaitu jenis ice breaking apa yang cocok untuk pelajaran Bahasa Indonesia, dan terakhir ingin mengetahui pengaruh ice breaking terhadap minat belajar Bahasa Indonesia siswa kelas IV MI Muhammadiyah Sukajati Haurgeulis. Penelitian ini bertujuan untuk mengetahui minat belajar Bahasa Indonesia siswa kelas IV pada MI Muhammadiyah Sukajati Haurgeulis., penelitian ini juga dilakukan untuk mengetahui jenis ice breaking apa saja yang cocok untuk pelajaran Bahasa Indonesia, dan untuk mengetahui adakah pengaruh ice breaking terhadap minat belajar Bahasa Indonesia siswa kelas IV MI Muhammadiyah Sukajati Haurgeulis. Penelitian ini menggunakan pendekatan kuantitatif dengan teknik observasi, angket, dan dokumentasi. Populasi dalam penelitian ini yaitu siswa kelas IV MI Muhammadiyah, dan sampelnya yaitu 15 siswa kelas A sebagai kelas eksperimen dan 15 siswa kelas B sebagai kelas kontrol. Hasil penelitian ini menunjukkan bahwa adanya pengaruh ice breaking yang signifikan terhadap minat belajar Bahasa Indonesia pada siswa kelas IV. Hasil uji regresi linear sederhana menunjukkan nilai signifikansi yaitu Sig. 0,000 < 0,05 maka dapat disimpulkan bahwa terdapat pengaruh antara variabel bebas terhadap variabel kontrol sebesar 70%. Hasil uji hipotesis nilai Asymp.Sig. (2-tailled) sebesar 0,002 < 0,05 maka dikatakan bahwa H0 ditolak dan H1 diterima. Ice breaking yang relevan dalam pembelajaran Bahasa Indonesia yaitu ice breaking yang direncanakan terlebih dahulu dan dikolaborasikan dengan materi yang akan diajarkan.Kata kunci: Ice Breaking, Minat Belajar, Bahasa Indonesia